1994
DOI: 10.1111/j.2042-3306.1994.tb04351.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the transportin vitroof lysine, histidine, arginine and ammonia across the mucosa of the equine colon

Abstract: Summary Discs of stripped mucosa from the proximal ventral colon were prepared immediately after slaughter of 8 Shetland cross‐breed ponies. The mucosae were fixed in incubation chambers and used in incubation experiments to study the transmucosal fluxes of the amino acids lysine, histidine and arginine (150 min) and of ammonia (90 min). When the amino acid concentrations in the mucosal solution were in the physiological range (2.8–3.0 mmol/l) no transport to the serosal side of the tissue was found. When the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
1
10
1
Order By: Relevance
“…Studies of L-Lys uptake by the equine large intestine using both in vivo and in vitro methods have yielded contradictory results (Slade et al, 1971;Bochröder et al, 1994). Our results support those of Slade et al (1971), who demonstrated appearance of labeled Lys and other essential AA in the cecal vein after cecal in-fusion of '"'N-labeled microbes in a pony.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Studies of L-Lys uptake by the equine large intestine using both in vivo and in vitro methods have yielded contradictory results (Slade et al, 1971;Bochröder et al, 1994). Our results support those of Slade et al (1971), who demonstrated appearance of labeled Lys and other essential AA in the cecal vein after cecal in-fusion of '"'N-labeled microbes in a pony.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, it is possible that b""''AT is responsible for L-Lys uptake from the intestinal lumen in both the jejunum and colon of the horse. On the other hand, transmucosal potential difference of L-Lys, L-His, and L-Arg measured across proximal colonie discs was low, indicating minimal transport of these AA (Bochröder et al, 1994). Also, Freeman et al (1989) Wnd no transport of L-Ala determined with transmucosal potential difference across cecal mucosa harvested from horses.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Bochroder et al (1994) reported that the colon epithelium of the horse is not permeable for histidine, lysine and arginine. Schmitz et al (1991) found arginine absorption from the caecum of cow, pig and horse below 10%.…”
Section: Contrary To the Results Ofmentioning
confidence: 99%
“…There is evidence that substantial quantités of microbial and feed protein are digested in the large intestine and that nitrogen is absorbed predominantly in the form of ammonia (Zebrowska, 1975;Dixon and Nolan, 1982;Schmitz et al, 1991;Bochroder et al, 1994). Some reports show that amino acids can be absorbed from the caecum of pigs and mice (Robinson et al, 1973;Olszewski, 1975;James and Smith, 1976;Jarvis et all., 1977), but data is lacking on the absorption of amino acids from the large intestine of sheep.…”
Section: Introductionmentioning
confidence: 99%